Risiko Tinggi Dislipidemia pada Remaja Obesitas: Menggali Faktor dan Implikasinya terhadap Kesehatan Kardiovaskular (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
Dyslipidemia in obese adolescents is a marker of early-onset cardiovascular problems such as atherosclerosis. The purpose of this study was to identify the magnitude of the problem of dyslipidemia in obese adolescents. This study uses content analysis of literature reviews in synthesizing articles in accordance with the criteria and research objectives. This study uses Google Scholar, Pub Med using the keywords "Youth Dyslipidemia". Articles included in the inclusion criteria are original research, which measures cholesterol levels in adolescents. , whereas we were excluded if the articles contained narrative opinion articles, editorial comments, literatru reviews, and did not measure cholesterol levels in adolescents. The results from 18,900 articles we get about 8 articles of which 3 articles about dyslipidemia in adolescents with diabetes, 3 articles on dyslipidemia in healthy adolescents, and 2 articles on the magnitude of the problem of dyslipidemia in adolescents with lipid abnormalities. Adolescents who are obese have a high risk of developing dyslipidemia, which is a disorder of lipid metabolism. Dyslipidemia in obese adolescents contributes to atherosclerosis, namely the formation of plaque that settles in blood vessels and can cause cardiovascular disease.